Obsessive Beliefs in Panic Disorder Patients - (:unkn) unknown (AVES, 2013)
Background: Cognitive models highlight the role of obsessive beliefs in the development of obsessive-compulsive disorder (OCD) and the prognosis. But some studies suggested that these beliefs are not specific to OCD; generally may be a common feature of anxiety disorders and depression. In these studies, anxiety disorders were not studied separately, but were used as mixed samples. This study aims to investigate obsessive beliefs only in patients with panic disorder. Method: In this study, we enrolled 101 patients who were diagnosed with panic disorder and 155 healthy volunteers. The patients were divided into two subgroups according to the cut-off point of the panic and agoraphobia scale (PAS) scores:, group 1 - with scores <= 11 and group 2 - with scores >= 12. Both subgroups and control group were compared for obsessive beliefs assessed with the Obsessive Beliefs Questionnaire-44 (OBQ-44) and also compared while evaluating the mixed effects of state-trait anxiety and depression. Results: Group 2 had higher total and subscale scores on OBQ-44 than group 1 and controls. Presence of agoraphobia made a statistically significant difference only for the responsibility/threat estimation subscale scores. When trait anxiety level was under control, significant difference was maintained for OBQ-44 subscales, while when state anxiety level and depression were under control, only importance of thought/controlling thoughts was statistically significant Conclusion: Trait anxiety and depression affect all obsessive beliefs except for 'importance of thought/controlling thoughts' subscale of OBQ-44. We think that obsessive beliefs are not specific to OCD. Obsessive beliefs may have a common role in the development of trait anxiety and depression. We assume that further studies investigating obsessive beliefs in other anxiety disorders and depression might be enlightening.
Keywords: Panic Disorder; Obsessive beliefs; OBQ-44; COMPULSIVE SYMPTOMS; AGORAPHOBIA